Proposta de um sistema de proteção para preservar a coordenação entre religadores e elos fusíveis de sistemas de distribuição na presença de geração distribuída - Gutierres, Luiz Fernando de Freitas (2013)
This work presents a novel recloser-fuse coordination protection for distributed generation systems based on the use of RMS current comparators. In real-time, these comparators are responsible for analyzing current magnitude in upstream and downstream network directions; identify faults; and assess the recloser-fuse coordination status based on critical margins identified by the protection system. Once a miscoordination is detected, some distributed generation units are strategically disconnected from the distribution network by gate turn-off thyristors. As a result of this action, short-circuit current is reduced to a satisfactory level, restoring the coordination between recloser and fuses in the grid. The proposed protection system has been implemented in a 12.47-kV grid and simulations have been carried out in ATP/EMTP. The main contributions in this work are the results obtained mainly throughout testing fault circumstances and operational conditions. Besides, this work proposes a protection methodology in the perspective of a national standardized regulation. Significantly, the approach contributes to the adequacy and modernization of distribution systems with considerable tendency of distributed generation insertion.